CO-CAVITY pilot survey: molecular gas and star formation in void galaxies - Domínguez-Gómez, José; Lisenfeld, U.; Pérez, I.; López-Sánchez, Á R.; Puertas, S. Duarte; Falcón-Barroso, J.; Kreckel, Kathryn; Peletier, R. F.; Ruiz-Lara, T.; Weygaert, R. van de; Hulst, J. M. van der; Verley, S. (Astronomy and astrophysics, 2022)
Voids are the most under-dense large-scale regions in the Universe. Galaxies inhabiting voids are one of the keys for understanding the intrinsic processes of galaxy evolution, as external factors such as multiple galaxy mergers or a dense self-collapsing environment are negligible.Aims. We present the first molecular gas mass survey of void galaxies. We compare these new data together with data for the atomic gas mass (MH I) and star formation rate (SFR) from the literature to those of galaxies in filaments and walls in order to better understand how molecular gas and star formation are related to the large-scale environment.Methods. We observed at the IRAM 30 m telescope the CO(1−0) and CO(2−1) emission of 20 void galaxies selected from the Void Galaxy Survey, with a stellar mass range from 108.5 to 1010.3 M⊙. We detected 15 objects in at least one CO line. We compared the molecular gas mass (MH2), the star formation efficiency (SFE = SFR/MH2), the atomic gas mass, the molecular-to-atomic gas mass ratio, and the specific star formation rate (sSFR) of the void galaxies with two control samples of galaxies in filaments and walls, selected from xCOLD GASS and EDGE-CALIFA, for different stellar mass bins and taking the star formation activity into account.Results. In general, we do not find any significant differences between void galaxies and the control sample. In particular, we do not find any evidence for a difference in the molecular gas mass or molecular gas mass fraction. For the other parameters (SFE, atomic gas mass, molecular-to-atomic gas mass ratio, and sSFR), we also find similar (within the errors) mean values between void and filament and wall galaxies when the sample is limited to star-forming galaxies. We find no evidence for an enhanced sSFR in void galaxies. Some tentative differences emerge when trends with stellar mass are studied: The SFE of void galaxies might be lower than in filament and wall galaxies for low stellar masses, and there might be a trend of increasing deficiency in the HI content in void galaxies compared to galaxies in filaments and walls for higher stellar masses, accompanied by an increase in the molecular-to-atomic gas mass ratio. However, all trends with stellar mass are based on a low number of galaxies and need to be confirmed for a larger sample.Conclusions. The results for the molecular gas mass for a sample of 20 voids galaxies allowed us to make a statistical comparison to galaxies in filaments and walls for the first time. We do not find any significant differences of the molecular gas properties and the SFE, but we note that a larger sample is necessary to confirm this and be sensitive to subtle trends.
Gesehen am 20.04.2022